(untitled) (Research, Society and Development, 2020)
Infection caused by the Human Immunodeficiency Virus affects approximately 34 million people worldwide and is responsible for the Acquired Immunodeficiency Syndrome. In Brazil, there is an increase in the number of elderly people with the Human Immunodeficiency Virus (HIV). Because it is an incurable disease, it has a major impact on public health and the quality of life of these patients. The study aims to report the impact on quality of life in elderly people with HIV. It is an integrative review with seven articles selected in the Bdenf and SciELO databases between 2010 and 2020. After reading, analyzing and interpreting the data, the publications showed different challenges faced by elderly people living with the diagnosis of HIV, however, also point to strategies to overcome the disease and improve quality of life. Knowing the barriers related to the adequate treatment of physical and psychosocial illness, among other demands in the social context, can be an important tool in the search for ways to offer higher quality assistance to this population.